Komunikasi Budaya dalam Gaya Manajemen Konflik di Era Globalisasi - Sasmi, Nanda Adjeng Castity Nur Aziza; Razani, Nabilah Ananda; Sulthanah, Qonitah Arya; Ariadi, Sandi Dwi (Universitas Prof. Dr. Moestopo (Beragama), 2024)
The era of globalization and high mobility has transformed the dynamics of communication, particularly in intercultural communication. This study aims to evaluate the relevance of face-negotiation theory in a modern context through a systematic literature review of selected journal articles. The method employed involves collecting relevant evidence and examining the differences in perceptions between Eastern and Western cultures, as well as their influence on face selection strategies and conflict management styles. The findings indicate that face-negotiation theory plays a significant role in explaining cross-cultural communication patterns but faces challenges in terms of flexibility and adaptation to changing times. This theory is deemed in need of updates to remain relevant, especially in an era marked by increasing pluralism and digital communication. Furthermore, of the five theoretical implications proposed, only three have been addressed in previous studies. This study recommends further research to explore the application of face-negotiation theory in communication mediated by digital technology to broaden insights into cross-cultural communication studies in the modern era.